Effects of intervention to mild GDM on outcomes. (May 2015) - Wei, Yu-Mei; Yang, Hui-Xia; Zhu, Wei-Wei; Yang, Hong-Yun; Li, Hai-Xia; Kapur, Anil
Abstract Objective: To evaluate pregnancy outcomes in women with gestational diabetes mellitus (GDM) diagnosed by the IADPSG criteria at 24–28 weeks of gestation but with fasting plasma glucose (FPG) less than 4.4 mmol/L. Research design and methods: A retrospective study was conducted. Medical records of 25 674 pregnant women attending the Peking University First Hospital (PUFH) were analyzed. Women with FPG value <4.4 mmol/L were segregated into those with and without GDM based on the IADPSG criteria. Pregnancy outcomes in the form of birth weight, neonatal hypoglycemia and cesarean delivery were compared between the two groups. Results: The incidence of macrosomia between GDM 7.1% (treated 6.9%; untreated 7.2%) was not different from the non GDM group 6.3%, similarly neonatal hypoglycemia 1.9% (treated 2.0%; untreated 1.7%) was were not significantly different from the non GDM group 1.1%. Rate of cesarean delivery in the untreated GDM group 59.7% was significantly higher compared to both with treated GDM (48.4%) and the non GDM group (47.6%). Conclusions: There is no difference in the incidence of select adverse pregnancy outcomes amongst Chinese women with mild GDM (FPG<4.4 mmol/L) with or without intervention compared to women without GDM.